Experimental Study on the Shear Strength of Different Interfaces of Fine-Grained-Tailing-Filled Geotextile Tubes - Xiaowen Liu; Zeming Wu; Feiyang Guo (Buildings, 2024)
As damming material, fine-grained tailings present challenges such as low dam strength and poor stability. To address these issues, this study employs geotextile tube technology to mix water with fine-grained tailings, forming a tailing slurry with a concentration of 60%, which is filled into a geotextile bag to form a geotextile tube, so as to improve the stability of fine-grained tailings. The shear strength characteristics of each interface under different consolidation times and different filling degrees were studied via an indoor shear experiment, including the shear strength of tailing particles, that between tailings and geotextiles, and that within geotextile tubes themselves. The results show that the shear strength of each interface conforms to the Mohr–Coulomb strength criterion, and that the interface cohesion is greatly affected by the consolidation time, while the interface friction angle is mainly affected by the filling degree. Moreover, the shear strength comparison, based on the comprehensive friction angle concept, indicates a substantial increase in shear strength at the interfaces between geotextile tubes compared to both that of the tailings themselves and the interface between tailings and geotextiles, highlighting the reinforcing effect of the geotextile tube filling technology on tailings’ shear strength.